Polityka i soft power w piłce nożnej – na czym polega zjawisko sportswashingu? .......... 217 - Muraszow, Jan (Oblicza dyplomacji, 2025)
POLITICS AND SOFT POWER IN FOOTBALL: WHAT IS SPORTWASHING?The issue of sportswashing is not often addressed in analyses of global sport, or international relations more broadly. It is one of the many aspects of unethical actions taken by states to hide internal or external abuses and conflicts. Among soft power activities, it is precisely any activity related to sport that is gaining in popularity, due to its globalization, the ease of influence over sports associations and the general positive connotations of involvement in sport development. For this reason, it is important to draw attention to the negative aspects and abuses of state activity within sport – including the topic of sportswashing addressed by the author. The aim of this article is to provide an insight into this overlooked, but important, issue in the involvement of states in the operation of football competitions.